The Emerging Facets of Non-Cancerous Warburg Effect - Abdel-Haleem, Alyaa M.; Lewis, Nathan E.; Jamshidi, Neema; Mineta, Katsuhiko; Gao, Xin; Gojobori, Takashi (Frontiers in Endocrinology, 2017)
The Warburg effect (WE), or aerobic glycolysis, is commonly recognized as a hallmark of cancer, and has been extensively studied for potential anti-cancer therapeutics development. Beyond cancer, the WE plays an important role in many other cell types involved in immunity, angiogenesis, pluripotency, and infection by pathogens (e.g., malaria). Here, we review the WE in noncancerous context as a ‘hallmark of rapid proliferation’. We observe that WE operates in rapidly dividing cells in normal and pathological states as well as in pathological states that are triggered by internal and external cues. Aerobic glycolysis is also the preferred metabolic program in the cases when robust transient responses are needed. We aim to draw attention to the potential of computational modeling approaches in systematic characterization of common metabolic features beyond WE across physiological and pathological conditions. Identification of metabolic commonalities across various diseases may lead to successful repurposing of drugs and biomarkers.